2023
DOI: 10.1101/2023.04.17.537043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Mapping of SNP Markers and Candidate Genes Associated with Day-Neutral Flowering inCannabis sativaL.

Abstract: Hemp (Cannabis sativaL.) is a primarily short-day crop grown for grain, fiber, and secondary metabolites. Although terminal flowering of most non-domesticated hemp is regarded as photoperiod sensitive, limited germplasm is available for the development of day-neutral hemp. Day-neutral plants experience flower maturation independently of the short-day photoperiod cue which is typically triggered by photoperiods of less than 14 hours. The day-neutral trait is the subject of increased commercial interest for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…In Arabidopsis and rice many tested populations show segregation distortion, which may be due to seed dormancy and lethal epistatic interactions 24,25 . However, the segregation distortion could be the result of the SV noted across the pangenome, and consistent with this chromosome 1, where DN alleles have been mapped 21,26 , displays the largest size variation (Supplemental Fig. 4).…”
Section: Mainsupporting
confidence: 72%
See 2 more Smart Citations
“…In Arabidopsis and rice many tested populations show segregation distortion, which may be due to seed dormancy and lethal epistatic interactions 24,25 . However, the segregation distortion could be the result of the SV noted across the pangenome, and consistent with this chromosome 1, where DN alleles have been mapped 21,26 , displays the largest size variation (Supplemental Fig. 4).…”
Section: Mainsupporting
confidence: 72%
“…1b). Segregation distortion patterns observed across many regions of the genome were noted in a prior study of this population 21 , and may be caused by differences in seed germination rates. A study done by Beutler and Der Marderosian reported a delay in seed germination in crosses between DN and SD plants; the authors speculate this trait is a carryover from the hypothesized species “ Cannabis ruderalis ,” or DN, parent 22 .…”
Section: Mainmentioning
confidence: 51%
See 1 more Smart Citation
“…Two recent mapping studies have suggested C. sativa homologues of APETALA2 and PSEUDO-RESPONSE REGU-LATOR 37 (PRR37) as candidate genes within Autoflower1 (Garfinkel et al, 2023;Leckie et al, 2023). Alterations of PRR37 homologues in T. aestivum, O. sativa, and Sorghum bicolor are known to confer photoperiod insensitivity due to de-repressed FT expression (Beales et al, 2007;Koo et al, 2013;Murphy et al, 2011).…”
Section: Photoperiod Insensitivity Originated Multiple Times Independ...mentioning
confidence: 99%